The Analysis of the Impact of Profitability and Liquidity on Enterprise Value in Main Board Real Estate Companies Listed on the IDX for the 2021-2025 Period - Fera Tjahjani Fera; Lidia Andiani Lidia (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of Profitability and Liquidity on Enterprise Value in a business entity. A quantitative approach is used as a type of research to test the causal relationship between variables. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, a variance-based structural equation modeling technique that is highly suitable for exploring predictive and causal relationships in complex models. The results show that both Profitability and Liquidity have a positive and significant influence on Enterprise Value. Profitability, as measured by Return on Assets (ROA) and Return on Equity (ROE), is proven to substantially contribute to increasing company value. Similarly, Liquidity, as indicated by the Current Ratio (CR), also significantly and positively affects Enterprise Value. This finding is supported by the positive path coefficient value and the T-statistic and P-value indicating a high level of significance, indicating that managerial decisions in optimizing Profitability and Liquidity are crucial to increasing overall company value.